2014
DOI: 10.1103/physrevlett.113.118101
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Deformation of Live Cells Induced by Pressure-Activated Cross-Membrane Ion Transport

Abstract: In this work, we developed a method that allows precise control over changes in the size of a cell via hydrostatic pressure changes in the medium. Specifically, we show that a sudden increase, or reduction, in the surrounding pressure, in the physiologically relevant range, triggers cross-membrane fluxes of sodium and potassium ions in leukemia cell lines K562 and HL60, resulting in reversible volumetric deformation with a characteristic time of around 30 min. Interestingly, healthy leukocytes do not respond t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 32 publications
(34 reference statements)
3
54
0
Order By: Relevance
“…Here, we document that under compressive stress, multicell spheroids as well as cell monolayers will decrease their intracellular tonicity by effluxing sodium, and that although cytoskeletal filaments do not actively support compressive stress, actin polymerization is required for osmotic regulation. This finding is consistent with the work of Hui et al (12), who found that increased hydrostatic pressure induced active sodium efflux. Recent studies using C. elegans suggested that these organisms may have an absolute internal pressure set point (16).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Here, we document that under compressive stress, multicell spheroids as well as cell monolayers will decrease their intracellular tonicity by effluxing sodium, and that although cytoskeletal filaments do not actively support compressive stress, actin polymerization is required for osmotic regulation. This finding is consistent with the work of Hui et al (12), who found that increased hydrostatic pressure induced active sodium efflux. Recent studies using C. elegans suggested that these organisms may have an absolute internal pressure set point (16).…”
Section: Discussionsupporting
confidence: 91%
“…2 B). This is consistent with previous studies that showed that hydrostatic pressure induces sodium efflux (12). Repeating this Biophysical Journal 109 (7) 1334-1337 experiment with modulation of actin filaments revealed that actin depolymerization blocked sodium efflux to a similar degree as NHE1 blockade.…”
Section: Sodium Efflux Under Compressive Solid Stresssupporting
confidence: 90%
“…Interestingly, atomic force microscopy-based studies have demonstrated that the energy density of individual dormant cells (i.e., Bacillus spores) in response to cyclic humidity variations is at least one order of magnitude higher than any synthetic materials including DEs . Live cells were shown to volumetrically shrink or swell via cross-membrane ion transport upon applied mechanical pressure (Hui et al, 2014). These results highlight the distinct advantage of involving biologically based materials in DE actuation and energy harvesting, and open a new avenue to build DE-made soft machines with tunable mechanical, chemical as well as electrical properties to generate active force/ motion at the (sub)cellular scale for potential applications in biomaterials and biointerfaces Zhang et al, 2013).…”
Section: Concluding Remarks and Outlookmentioning
confidence: 91%
“…With the evolution of c Lþ at hand, the volumetric change of cells can then be determined by tracking the water efflux from (or influx into) the cell (9). Specifically, treating the cell as a droplet enclosed by an elastic membrane layer, permeable to water molecules only, its size change can be described by…”
Section: Theoretical Model Of Cell-size Manipulation By Electroosmotimentioning
confidence: 99%
“…Currently, the most convenient and popular way to alter the cellular volume is via osmotic shocks, that is, by the sudden addition/withdrawal of salt to/from the culture medium (6)(7)(8). Interestingly, a recent study has revealed that variations in the surrounding hydrostatic pressure can also lead to volumetric change of live cells (9). A common theme of these approaches is that, essentially, a step change to the microenvironment of cells (i.e., osmolarity or hydrostatic pressure) is introduced.…”
Section: Introductionmentioning
confidence: 98%